MODERN APPROACHES TO THE DEVELOPMENT AND USE OF BIOCOMPATIBLE IMPLANTS: MATERIALS, TECHNOLOGIES AND PROSPECTS - Farkhodjon Khusenovich, Mamatkulov (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aims to evaluate the osseointegration potential of stainless steel implants manufactured using additive technologies for tibial prosthetics in rabbits, focusing on mechanical stability and bone-implant integration. Method: The experimental study was conducted on six chinchilla rabbits aged 6–8 months. Under general anesthesia, each rabbit underwent leg amputation followed by the implantation of a screw-type stainless steel implant produced through additive manufacturing. The implants were stabilized using the Ilizarov apparatus for six weeks. Clinical assessments, radiological imaging, and histological analyses were performed to evaluate the extent of osseointegration. Results: The findings demonstrate that the screw-type implant structure successfully osseointegrated into the tubular bone, with significant new bone tissue formation observed on the implant surface after 12 weeks. This bone-implant integration formed a stable bone-implant block capable of withstanding mechanical stress, confirming the implant's mechanical stability within the bone. Novelty: This study highlights the promising potential of additive manufacturing technologies in producing biocompatible implants with enhanced osseointegration capabilities, paving the way for more effective and durable orthopedic prosthetics.